2015
DOI: 10.1097/mao.0000000000000575
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Active Opening of the Eustachian Tube in a Hypobaric/Hyperbaric Pressure Chamber

Abstract: Standard values for the opening pressure of the tube and the tube opening duration for active tubal openings (Valsalva maneuver, swallowing) were described, and typical curve gradients for healthy subjects could be shown. This is another step toward analyzing the function of the tube in compression and decompression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 25 publications
1
26
0
2
Order By: Relevance
“…Therefore, participants were asked to swallow if they felt discomfort in the ear. Our research group was the first to show that it was possible to measure standard data in the active equalization system (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, participants were asked to swallow if they felt discomfort in the ear. Our research group was the first to show that it was possible to measure standard data in the active equalization system (24).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, data for ET parameters of the passive and active tube opening were published on healthy participants in a pure hypobaric pressure chambers (21Y23). Our research group obtained standard values for ET parameters of the passive and active tube opening in a combined hypobaric/hyperbaric pressure chamber (12,24). In this study, we measured the same cohort (30 healthy participants) as we reported in the previous publication (24) but with a different hypothesis.…”
mentioning
confidence: 92%
“…Measurements were performed in hypobaric and hyperbaric environments. The pressure was set between 0.8 bar and 1.2 bar as established in different studies before …”
Section: Methodsmentioning
confidence: 99%
“…The test protocol contained phases of decompression (1 bar‐0.8 bar and 1.2 bar‐1 bar) and compression (0.8 bar‐1.2 bar). We described the utilised standard protocol in detail in former publications (Figure ) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation